Epidemiology of Spinal Trauma and Related Complication - Kathayat, Tufan Singh; Rokaya, Poojan Kumar; Rawal, Mangal; Marasini, Pawan; Karki, Prashanna Dip; Nath, Mohan (Journal of Nepal Health Research Council, 2024)
Background: Traumatic spinal injury is leading cause of mortality and morbidity among the people of productive age group. This study aim to find the cause of spinal injury, site ,and mode of injury, treatment option given so that a preventive measures and create awareness among people of this region. Methods: This is a prospective observation study done in Karnali Academy of Health Sciences from December 2021 to January 2023. Performa was filled to collect data. Data were entered in excel sheet and transported to SPSS 16.0 and statistical analysis was done .Results: Out of 117 patients male population had higher incidence of spinal trauma (69.2%) with average age 43.9 years . Fall injury was the commonest mode of injury. 65.8% had injury at the thoracolumbar junction followed by lumbar, thoracic and cervical respectively. Cervical injury patients had higher incidence of neurological deficit. The average duration of trauma to hospital presentation was 10.9±11.2 hours. 19.7 % were operated and 6.8 % of patients were referred to other center.Conclusions: Fall injury being the commonest mode of injury in this art of world, prevention and awareness should be raised about the spinal trauma and its consequences. Adequate equipment with health facilities to the distant hospital may reduce the referral rate and duration of presentation to the hospital which ultimately prevent the further damage to the cord.Keywords : Fall Injury; spinal trauma; western Nepal.